Observations of Magnetic Reconnection in the Transition Region of Quasi‐Parallel Shocks. Issue 3 (13th February 2019) - Gingell, I.; Schwartz, S. J.; Eastwood, J. P.; Burch, J. L; Ergun, R. E.; Fuselier, S.; Gershman, D. J.; Giles, B. L.; Khotyaintsev, Y. V.; Lavraud, B.; Lindqvist, P.‐A.; Paterson, W. R.; et al.
Abstract: Using observations of Earth's bow shock by the Magnetospheric Multiscale mission, we show for the first time that active magnetic reconnection is occurring at current sheets embedded within the quasi‐parallel shock's transition layer. We observe an electron jet and heating but no ion response, suggesting we have observed an electron‐only mode. The lack of ion response is consistent with simulations showing reconnection onset on sub‐ion time scales. We also discuss the impact of electron heating in shocks via reconnection. Plain Language Summary: For the first time, we document an observation of magnetic reconnection occurring at Earth's bow shock. The observations have been made by NASA's Magnetospheric Multiscale mission while the bow shock is under a "quasi‐parallel" geometry, which typically results in a highly disordered structure. Models of shock waves in space plasmas do not currently account for reconnection. This therefore introduces a new avenue of research into how shocks can repartition energy when slowing the solar wind from supersonic to subsonic flow. The observations also introduce a new regime for magnetic reconnection, for which we observe only an electron response at an ion scale reconnecting structure. This work will also attract interest from the broader astrophysics community, as reconnection at shocks may influence cosmic ray generation. Key Points: Reconnecting current sheets have been observed at a quasi‐parallel bow shock The ion‐scale current sheet exhibits only an electron jet and heating, with no ion response Consistent with kinetic simulations, reconnection relaxes complexity in the shock transition region